ANALYSIS OF EMPLOYEE ENGAGEMENT PRACTICES AND THEIR ROLE IN RETAINING HEALTHCARE PROFESSIONALS AT ISWARYA SUPER SPECIALITY HOSPITAL, CHENNAI - Dr. A. Alamelumangai, Dr. K. Valarmathi, Dr. P. Porseziyan, Dr. V. Govindarajan, Dr.P.Subburaj (South Eastern European Journal of Public Health, 2025)
This study explores the relationship between employee engagement and employee retention within healthcare organizations. By synthesizing existing literature, it explores how employee engagement initiatives impact employee retention rates, thereby influencing organizational effectiveness and patient outcomes. Employee engagement means commitment and motivation of employees to their work and the organization. Engaged employees are productive, innovative and commited to the success of the organization Employee engagement and retention are essential aspects in the performance and sustainability of healthcare businesses. Moreover, it elucidates the mechanisms through which heightened employee engagement fosters greater employee retention, including increased job satisfaction, commitment, and productivity. Quantitative analysis revealed a strong positive correlation between engagement levels and retention rates, suggesting that higher engagement leads to lower turnover. Qualitative findings further illuminated the mechanisms through which engagement fosters retention, including job satisfaction, organizational commitment, and supportive work environments. Overall, this research contributes to a deeper understanding of relationship between employee engagement and employee retention and its impact on employee retention which results in organizational outcomes such as employee turnover, increased productivity and organizational reputation